Analysis of the Total Biflavonoids Extract from Selaginella doederleinii by HPLC-QTOF-MS and Its In Vitro and In Vivo Anticancer Effects - Yao, Hong (Molecules, 2017)
Selaginella doederleinii Hieron has been traditionally used as a folk antitumor herbal medicine in China. In this paper, the phytochemical components of the total biflavonoids extract from S. doederleinii were studied by using high-performance liquid chromatography coupled with electrospray ionization quadrupole time-of-flight mass spectrometry (HPLC-ESI-QTOF MS/MS) in negative ion mode, and their in vitro and in vivo anticancer effects were evaluated. Four types of biflavonoids from S. doederleinii, including IC3′–IIC8′′, IC3′–IIC6′′, IC3′–IIC3′′′, and C–O linked biflavonoids were examined originally using QTOF MS/MS. The fragmentation behavior of IC3′–IIC3′′′ linked biflavonoids was reported for the first time. A total of twenty biflavonoids were identified or tentatively characterized and eight biflavonoids were found from S. doederleinii for the first time. Furthermore, the 3-(4,5-Dimethyl-2-thizolyl)-2,5-diphenyltertazolium bromide (MTT) assay and xenograft model of mouse lewis lung cancer(LLC) in male C57BL/6 mice revealed favorable anticancer properties of the total biflavonoids extracts from S. doederleinii. The results of this work could provide useful knowledge for the identification of biflavonoids in herbal samples and further insights into the chemopreventive function of this plant.